SISTEM INFORMASI PENGUKURAN MATRIKS ISO USABILITY TESTING BERBASIS WEB: STUDI KASUS SHOPEE - Rahma Fitria; Muhammad Ikhwani (STMIK KAPUTAMA, 2023)
The manual metric measurement is time-consuming due to the large number of users and test criteria. Additionally, not all tester is able to complete all metrics measurement correctly in time. Software testers can process and analyze test data much more easily when using information systems in conducting usability testing. The purposes of this study is to develop a web-based information system of ISO metrics measurement and conducting usability tests on the Shopee application with 10 users. The level of usability of the Shopee application is highly dependent on measuring user happiness with the application. Usability testing matrics measurements are based on ISO measures that include effectiveness, efficiency, and satisfaction. The system is feasible to use and runs normally, according to the calculation results interpreted based on the Likert Scale, which came to 66.924%. However, there are still many users who do not understand how to use the features. It’s expected that this research will help sotware tester to improve the quality in conducting usability testing as well as provide feedbacks from the user in order to elevate the ease of use of the application.